PENYELEKSI BARANG BERDASARKAN TINGGI BERBABIS MICROCONTROLLER ATMEGA 8535 DENGAN KONVEYOR - Krisnu Wardana, I Gede; Gunantara, Nyoman; Pramaita, Nyoman (Jurnal SPEKTRUM, 2019)
Problems that often occur in the selection of goods, there are still many industries that make convey-ors as senders only without a selection process. The purpose of this study was to make a high-variable item selection prototype tool using an ATMega 8535 microcontroller. It was found that the prototype goods se-lection tool was based on a high ATMega 8535 microcontroller with a maximum working conveyor. Con-veyor 1 will move if there is an item or object that is left in front of conveyor 1 and stops the goods at the end of the conveyor 1. Conveyor 2 will move if the photodiode sensor has detected the items on the convey-or 1. All tests are performed properly. The photodiode sensor works well to measure the height of objects or items. Further improvements with more complex development prototypes that can be applied to actual industries and factories. This tool can only measure the height of the item from what can be developed or the weight of the item.